Renal effects of Bunodosoma caissarum crude extract: Prostaglandin and endothelin involvement - Martins, René Duarte; Jorge, Roberta Jeane Bezerra; Alves, Renata de Sousa; Silva Neto, Antônio Gomes da; Barbosa, Paulo Sergio F.; Costa Martins, Alice Maria; Toyama, Marcos H. [UNESP]; Monteiro, Helena Serra Azul (Elsevier, 2017)
Sea anemones contain a variety of interesting biologically active compounds, including some potent toxins. PLA2 from Bunodosoma caissarum, a sea anemone endemic in the Brazilian southern coast, has shown renal alterations on isolated kidney. The aim of this study was to evaluate the renal and vascular effects of B. caissarum crude extract (BcE) on isolated perfused kidney and arteriolar mesenteric bed, as well the involvement of prostaglandins and endothelin. BcE did not show any effect on arteriolar mesenteric bed, but increased perfusion pressure, renal vascular resistance, urinary flow, glomerular filtration rate and decreased the percentage of sodium tubular transport on isolated perfused kidney. Indomethacin blocked the renal effects induced by BcE and tezosentan only partially blocked these effects. These results demonstrate the effects of BcE on kidney in situ, suggesting the involvement of prostaglandins and endothelin.
Keywords: Bunodosoma caissarum; Endothelin; Envenomation; Isolated perfused kidney; Prostaglandin; Sea anemone